A sociocultural analysis of the ethics of involving children in educational research. Issue 3 (4th March 2017) - Bourke, Roseanna; Loveridge, Judith; O'Neill, John; Erueti, Bevan; Jamieson, Andrew
ABSTRACT: This article explores the ethical complexities of involving children in research in the contexts of their families, schools and communities. We argue for an approach that is dynamic, reflexive, responsive and informed by an understanding of how local cultures impact on and shape negotiations and practices around ethical issues and processes. We use different sociocultural lenses to analyse the complexities of ethical processes and practices at the beginning of a research project which explored children's informal and everyday learning. The article contributes to ethical debates about involving children with research through foregrounding the multiplicities and complexities that emerge when researchers are attentive to the practices and values of the settings that children's and researchers' lives traverse.